Expanding the Genetic Code of Lactococcus lactis and Escherichia coli to Incorporate Non-canonical Amino Acids for Production of Modified Lantibiotics - Bartholomae, Maike; Baumann, Tobias; Nickling, Jessica H.; Peterhoff, David; Wagner, Ralf; Budisa, Nediljko; Kuipers, Oscar P. (Frontiers in Microbiology, 2018)
The incorporation of non-canonical amino acids (ncAAs) into ribosomally synthesized and posttranslationally modified peptides, e.g. nisin from the Gram-positive bacterium Lactococcus lactis, bears great potential to expand the chemical space of various antimicrobials. The ncAA Nε-Boc-L-lysine (BocK) was chosen for incorporation into nisin using the archaeal pyrrolysyl-tRNA synthetase (PylRS)-tRNAPyl pair to establish orthogonal translation in L. lactis for read-through of in-frame amber stop codons. In parallel, recombinant nisin production and orthogonal translation were combined in E. coli cells. Both organisms synthesized bioactive nisin(BocK) variants. Screening of a nisin amber codon library revealed suitable sites for ncAA incorporation and two variants displayed high antimicrobial activity. Orthogonal translation in E. coli and L. lactis presents a promising tool to create new-to-nature nisin derivatives.